Bestas e maravilhas: a visão emblemática dos animais na obra Historia animalium de Conrad Gesner e algumas de suas fontes - Klautau, Fabiana Dias (2014)
The purpose of this dissertation is the analysis of some aspects presented in Conrad Gesner´s Historia animalium (1551-1558), such as some information included in animal´s descriptions, its sources and images, as a vehicle of knowledge transmission. We intend to demonstrate that the content in Gesner´s work, as well as in his contemporary fellows, showed particular features which were consisted not only of anatomical and physiological animal´s descriptions, but they were especially comprised of information which today would be considered additional, as for example, what the ancients would say about each animal, the legends, the fables, its use in medicine, in culinary, in art, etc. All this correlated information was called, by some scholars of this period, the emblematic world view and they determined the scope of animal History in the sixteenth century. In order to demonstrate the interrelated information in Gesner´s writings, we selected not only his writings but also some works of other writers. One of them is Andrea Alciati´s Emblematum Libellus (1531), to which is attributed the dissemination of the emblems - a group of text and image designed to be deciphered, bringing intricate topics such as religion, love, betrayal, politics, moral, among others, which were widely covered in Gesner´s work. We also selected some examples of medieval bestiary to demonstrate how animals were described and illustrated in this kind of work, as well as Ovid´s (43 a.C 17 d.C) Ars Amatoria and the Methamorphoses, aiming at investigating this type of literature and, in later editions, the kind of images involving animals in these poems, in order to accomplish the case study about the mythical beast known as the Minotaur